Soft skills' influence on career development: exploring performance appraisal as a mediating mechanism - Grilo Dias, Andreia Filipa (My University, 2024)
In a progressively dynamic and competitive work environment, soft skills emerge as crucial elements for professional success. This investigation delved into the significance of these competencies in career development, employing performance appraisal as a mediating mechanism. The sample comprised 262 employed individuals. The study was operationalized through a quantitative methodology. Data were collected using the Short Skills Inventory, the Career Growth Scale, and the Performance Management Scale. The results demonstrated that the more developed the soft skills, the greater the likelihood of career progression for employees. Furthermore, it was found that performance appraisal significantly influences the professional trajectory of employees. The data also revealed that, by mediating the relationship between cross-functional skills and career advancement, performance appraisal enables the guidance and substantiation of strategic decisions within the organization.

Num contexto de trabalho cada vez mais dinâmico e competitivo, as soft skills emergem como elementos cruciais para o sucesso profissional. Esta investigação explorou a importância dessas competências no desenvolvimento de carreira, tendo a avaliação de desempenho como mecanismo de mediação. A amostra é constituída por 262 trabalhadores por conta de outrem. O estudo foi operacionalizado através de uma metodologia quantitativa. Os dados foram recolhidos através do Short Skills Inventory, do Career Growth Scale e da Performance Management Scale. Os resultados demonstraram quanto mais desenvolvidas se encontram as soft skills maior é a tendência para os colaboradores progredirem na carreira. Apurou-se, ainda, que a avaliação de desempenho exerce uma influência significativa na trajetória profissional dos colaboradores. Os dados também revelaram que ao mediar a relação entre as competências transversais e a progressão de carreira, a avaliação de desempenho permite orientar e fundamentar as decisões estratégicas da organização.
Keywords: Soft skills; Career development; Performance appraisal; Workplace context